The Role of Personal Branding in the Marketing Strategy of the Companies Operating in the Beauty and Fashion Industry - Dziagacz, Julia (Rola personal brandingu w strategiach marketingowych firm z branży kosmetycznej i modowej, 2025)
The article examines the strategic role of personal branding in the marketing efforts of companies within the beauty and fashion industries. By analysing case studies of outstanding figures like Chiara Ferragni, Molly-Mae Hague, David Beckham, Kim Kardashian, and Matilda Djerf, the study highlights how personal branding influences consumer behaviour, shapes brand perception, and drives market success. The findings suggest that personal branding, when effectively managed, can enhance corporate identity, foster consumer loyalty, and lead to greater market differentiation. The research underscores the importance of integrating personal branding into marketing strategies, particularly in industries where visual appeal and personal connection are paramount.
Quote as: Dziagacz, J. (2025). The Role of Personal Branding in the Marketing Strategy of the Companies Operating in the Beauty and Fashion Industry. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 56-66). Publishing House of Wroclaw University of Economics and Business.
Keywords: personal branding; marketing strategy; beauty industry; fashion industry; consumer behaviour; strategia marketingowa; przemysł kosmetyczny; przemysł modowy; zachowania konsumentów